Phytochemical profile, antimicrobial activity of nutmeg (Myristica fragrans Houtt.) seed extract and its efficacy as preservative for beef and shrimp - Lagha, Osama Mohamed Ben (2019)
Food preservation prevents the growth of foodborne pathogens, which can cause foodborne illness. Several methods already have been established for food preservation, such as using artificial food additives. However, application of artificial food additives in the long term could affect human health. This study aimed to evaluate extracts of nutmeg (Myristica fragrans Houtt.) seed against a range of foodborne pathogens: Escherichia coli ATCC25922, Listeria monocytogenes ATCC19112, Bacillus cereus ATCC33019, Pseudomonas aeruginosa ATCC9027, Vibrio parahaemolyticus ATCC17802, Bacillus pumilus ATCC14884, and Staphylococcus aureus KCCM12255. Then, identify the active antimicrobial compounds and phytochemical constituents in effective nutmeg seed extracts and evaluate their effectiveness as a preservative for raw beef and shrimp. The results showed that methanol extract of nutmeg seed exhibited antibacterial activity against Gramnegative and Gram-positive bacteria, with the diameter of the inhibition zone ranging between 9.02 ± 0.05–12.05 ± 0.50 mm. The nutmeg methanolic extract was more effective against B. cereus, B. pumilus, L. monocytogenes, E. coli, and S. aureus, with minimal inhibitory concentrations (MICs) of 0.15, 0.62, 0.62, 0.62 and 0.62 mg/mL, respectively, than V. parahaemolyticus and P. aeruginosa, with MICs of 2.5 and 1.25 mg/mL, respectively. However, this extract exhibited moderate minimal bactericidal concentration (MBC) against all tested bacteria. The kinetics of the time-kill assay of the methanolic extract Myristica fragrans Houtt. against the tested bacteria were not steady. In general, there no significant changes in viable cell count (Log10 CFU/mL) of bacteria treated with 0.5×MIC/0.5 h compared to the control. Additionally, the growth of V. parahaemolytics and B. pumilus bacteria showed steady kinetics when treated with 2×MIC. Complete killing of B. cereus cells treated with MIC, 2×MIC, and 4×MIC of the methanolic nutmeg extract was observed within 2, 2, and 4 h after treatment. Scanning electron microscope (SEM) analysis of representative pathogens showed that the 1% methanolic extract caused distortion of the bacteria, with changes in the external shape of the bacterial cells observed after 4 h, eventually leading to cell rupture after 24 h. Different solvent systems were evaluated by thin layer chromatography (TLC), hexane: ethyl acetate and chloroform: methanol in the ratios of 5:5, 8:2, 2:8, 7:3 and 9:1. The results showed that the solvent system of hexane: ethyl acetate (8:2) was the best solvent system for the distribution of the active compounds. In addition, all solvent systems showed positive results for the bioautography assay. Based on the microbial assay results, the active methanolic extract was analysed by gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS). GC-MS, identifying 36 compounds, with myristicin being the major compound (10.34%), followed by terpinene-4-ol (7.22%), tetradecanoic acid (5.66%), safrol (1.80%) and eugenol (0.32%). Results from the score plot (PCA) derived from the GC-MS data showed that the hexane extract and methanolic extract were related and distinct in comparison to the chloroform extract. Furthermore, partial least squares (PLS) score plots derived from GC-MS data showed that the tested bacteria statistically were more sensitive to particular active compounds. LC-MS, identifying the presence of active compounds including, limonene, γ-thujaplicin, palmitic amid and gingerol. Regarding the application, factorial design was employed and two storage conditions, 4oC and -18oC were used. The samples of beef and shrimp treated by 0.5%,1.5%,3% and 5% (v/w). The nutmeg extract in 1.5% and above significantly reduced the number of microflora and foodborne pathogens in beef and shrimp samples, and thereby extending the shelf life. The percentage of the reduction values in beef was between 71.81% and 99.75%. Meanwhile, the results ranging between 94.50% to 98.6% for the shrimp samples. Results showed that 1.5% of nutmeg extract maintained the thiobarbituric acid reactive substances (TBARS) and total volatile basic nitrogen (TVB-N) value at a minor level compared to the control samples. Regarding the sensory evaluations, 1.5% and 3% nutmeg extracts applied to raw and cooked samples were more acceptable to the panellists than the 5% nutmeg extract. In conclusion, nutmeg extract has the potential to be developed as a natural antimicrobial in food system as a natural alternative to synthetic preservatives.